Length of stay reduction in Intensive Care Unit associated with nursing care: Integrative literature review (Research, Society and Development, 2021)
Objective: To analyze the scientific evidence about the association between nursing care and reduced length of stay in intensive care units. Method: This is a bibliographic study of the integrative literature review type, carried out in the MEDLINE, BDENF and LILACS databases, from January 2015 to January 2020, and submitted to the prism flowchart methodology. The search identified 11 articles on the association between nursing care and reduced length of stay in adult intensive care units. Results: The prevention of adverse events, mobilization, carrying out the systematization of nursing care, delirium management and monitoring were identified as aspects capable of improving the patient's quality of life and reducing the length of stay in the intensive care unit. Conclusion: Nursing has an important role in providing critical care, its action aimed at preventing adverse events contributes to reducing the length of stay in intensive care units.